Crafting a Strong Research Design: A Step-by-Step Journey in Academic Writing (International Journal of Scientific Research and Management (IJSRM), 2024)
This study provides a comprehensive guide for researchers aiming to formulate a robust research design in academic writing. By addressing the definition, significance, and components of research design, this study aims to bridge the knowledge gap and equip researchers with the necessary tools to enhance the quality and reliability of their research. The originality of this study lies in its holistic approach, offering a step-by-step journey that covers various research methods and their suitability for different contexts, as well as crucial components of research design such as sampling strategies, data collection instruments, and data analysis techniques. By enhancing researchers’ understanding of research design, this study aims to empower them to produce high-quality research and make meaningful contributions to their fields of study.